Epidemiology of influenza under the coronavirus disease 2019 pandemic in Nanjing, China. Issue 5 (8th January 2022) - Wu, Kangjun; Wu, Xiaoqing; Wang, Weixiang; Hong, Lei
Abstract: Purpose: Since the pandemic of coronavirus disease‐19 (COVID‐19), the incidence of influenza has decreased significantly, but there are still few reports in the short period before and after the pandemic period. This study aimed to explore influenza activity and dynamic changes before and during the pandemic. Methods: A total of 1 324 357 influenza‐like illness (ILI) cases were reported under the ILI surveillance network from January 1, 2018, to September 5, 2021, in Nanjing, of which 16 158 cases were detected in a laboratory. Differences in ILI and influenza were conducted with the χ 2 test. Results: The number of ILI cases accounted for 8.97% of outpatient and emergency department visits. The influenza‐positive ratio (IPR) was 7.84% in ILI cases. During the COVID‐19 pandemic, ILI% and IPR dropped by 6.03% and 11.83% on average, respectively. Besides this, IPR rose slightly in Week 30–35 of 2021. Not only differences in gender, age, and employment status, but also the circulating strains had changed from type A to B through the COVID‐19 pandemic. Conclusion: The level of influenza activity was severely affected by COVID‐19, but it seems that it is inevitable to be vigilant against the co‐circulation in the future. Key Points: Influenza activity appeared lower in 2020–2021 than that in 2018–2019. Differences may have changed in age, gender, employment status for influenza‐positive ratio, and influenza virus types. Influenza activity may have been gradually rising. It may be necessary to be alert to the co‐circulation of influenza and COVID‐19.